Analysis of the Short Form-36 Questionnaire and Approbation of Proposals for Adaptation to the Kazakh Language - Yerbolat Saruarov; Gulnaz Nuskabayeva; Mehmet Ziya Gencer; Zhanat Shalkharova; Kaldybay Idrissov (Wolters Kluwer Medknow Publications, 2024)
Introduction: The objective of this study was to analyze the psychometric properties of the Kazakh translation of the Short Form-36 (SF-36) v2 Health Survey and evaluate its suitability for assessing health-related quality of life (QoL) in the Kazakh population. Methods: The SF-36 Health Survey version 2 (SF-36 v2) was administered to a sample of 632 Kazakh adults (442 women and 190 men) ranging in age from 27 to 69 years. Internal consistency reliability was evaluated using Cronbach's alpha. Scaling assumptions were examined through item-scale correlations. Scale scores were computed, and norm-based scoring was applied. The 2-week test-retest reliability was assessed in a subsample (n = 100) using intraclass correlations (ICCs). Results: Cronbach's alpha for the eight SF-36 v2 scales ranged from 0.760 to 0.947, indicating good to excellent internal consistency. All scales met scaling assumptions. Scaling success rates, where item-scale correlations exceeded 0.40, were 100% across scales. The physical component summary and mental component summary scores demonstrated high reliability (ICC = 0.94 and 0.91). The mean scale scores ranged from 66.6 (vitality) to 82.2 (physical functioning), with negative skewness observed for most scales. Conclusion: The Kazakh version of the SF-36 v2 demonstrated strong psychometric performance, with results supporting score reliability and construct validity in the Kazakh general population sample. This study provides evidence for the usability of the adapted SF-36 v2 in assessing health-related QoL among Kazakhs.